Determinan Tingkat Kemiskinan di Kabupaten Halmahera Selatan - Aprisal Boci; Chairullah Amin; Said Mala; Nonce Hasan; Nurdin I. Muhammad; Musdar Muhammad (Syntax Corporation Indonesia, 2024)
Development index, open unemployment rate, and labor force participation rate on poverty. The results of this study show that economic growth, open unemployment rate, and labor participation rate have no effect on the human development index partially or simultaneously. Meanwhile, economic growth, human development index, open unemployment rate, and labor participation level affect poverty partially or simultaneously.